Neutrophil extracellular traps drive peritoneal inflammation and tissue remodeling in pediatric peritoneal dialysis - Dücker, Charlotte Maria; Herrmann, Martin; Boettcher, Susanne; Bauer-Carmona, Sarah; Schild, Raphael-Sebastian; Schönfeld, Lavinia; Raluy, Laia Pagerols; Reinshagen, Konrad; Schmitt, Claus P.; Bartosova, Maria; Boettcher, Michael (Pediatric nephrology, 2025)
Peritoneal dialysis (PD) sustains children with chronic kidney disease stage 5 (CKD5) but promotes peritoneal membrane remodeling. Neutrophil extracellular traps (NETs) orchestrate antimicrobial defense and sterile inflammation; their involvement in PD-induced transformation is unknown.